The political construction of public health nutrition problems: a framing analysis of parliamentary debates on junk-food marketing to children in Australia. Issue 11 (17th August 2020) - Russell, Cherie; Lawrence, Mark; Cullerton, Katherine; Baker, Phillip
Abstract: Objective: Junk-food marketing contributes significantly to childhood obesity, which in turn imposes major health and economic burdens. Despite this, political priority for addressing junk-food marketing has been weak in many countries. Competing interests, worldviews and beliefs of stakeholders involved with the issue contribute to this political inertia. An integral group of actors for driving policy change are parliamentarians, who champion policy and enact legislation. However, how parliamentarians interpret and portray (i.e. frame) the causes and solutions of public health nutrition problems is poorly understood. The present study aimed to understand how Australian parliamentarians from different political parties frame the problem of junk-food marketing. Design: Framing analysis of transcripts from the Australian Government's Parliamentary Hansard, involving development of a theoretical framework, data collection, coding transcripts and thematic synthesis of results. Settings: Australia. Participants: None. Results: Parliamentarian framing generally reflected political party ideology. Liberal parliamentarians called for minimal government regulation and greater personal responsibility, reflecting the party's core values of liberalism and neoliberalism. Greens parliamentarians framed the issue as systemic, highlighting the need for government intervention and reflecting the core party value of social justice. Labor parliamentarians used both frames at varying times. Conclusions: Parliamentarians' framing was generally consistent with their party ideology, though subject to changes over time. This project provides insights into the role of framing and ideology in shaping public health policy responses and may inform communication strategies for nutrition advocates. Advocates might consider using frames that resonate with the ideologies of different political parties and adapting these over time.